2015
DOI: 10.1021/acs.jpcc.5b09643
|View full text |Cite
|
Sign up to set email alerts
|

Strain Assessment in Graphene Through the Raman 2D′ Mode

Abstract: Accurate and simple local strain assessment in graphene is one of the crucial tasks in device characterization. Raman spectroscopy is often used for that purpose through monitoring of the G and 2D modes. However, the shifts of those two bands might be biased, especially under uniaxial strain, by the effects of charge-transfer doping. Therefore, it is extremely desirable to use another Raman band, less affected by doping, but with a defined and measurable behavior under strain.The Raman 2D' mode is in this sens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…The real strain, calculated by multiplying the stress transfer efficiency and the maximum achieved nominal strain ϵ m .…”
Section: Resultsmentioning
confidence: 99%
“…The real strain, calculated by multiplying the stress transfer efficiency and the maximum achieved nominal strain ϵ m .…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have demonstrated that such Raman peak shis are associated with deection, strain, or doping. [41][42][43] In our experiment, strain might be induced when graphene was transferred onto PE lm, which would result in an upshi of the 2D peak.…”
Section: Process Assemblymentioning
confidence: 82%
“…-We have seen this splitting also in the width increase of the 2D' peak around a graphene nanoconstriction (fig S11) and this peak is said to be much less sensitive to doping effect 27 than the G peak.…”
Section: Peak Shift Variationmentioning
confidence: 86%
“…Due to the 2D nature of graphene, the thermal transport and phonon behavior is neither diffusive nor ballistic 25 and thermal conductivity unexpectedly depends on the sample size 26 . As a consequence, the geometry of the devices strongly affects the thermal conduction behavior which is still under debate [25][26][27] . In order to connect the porosity of our nanostructures and their thermal conductivity, we have also studied the Raman peak behavior of our devices under laser heating, at different powers (see Figure 3).…”
Section: Figurementioning
confidence: 99%